y/3-x/2=1

Simple and best practice solution for y/3-x/2=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y/3-x/2=1 equation:


x in (-oo:+oo)

y/3-(x/2) = 1 // - 1

y/3-(x/2)-1 = 0

1/3*y-1/2*x-1 = 0 // - 1/3*y-1

-1/2*x = -(1/3*y-1) // : -1/2

x = (-(1/3*y-1))/(-1/2)

x = -2*(1-(1/3*y))

x = -2*(1-(1/3*y))

See similar equations:

| 1.2x+0.3y=3.8 | | (5z^6x^5)/(8z^2)*(1x^3)/(3z^2x^3) | | v(m)=34000-0.2m | | 6.5-4.5(1+9.5b)=23.5 | | log(x-5)-log(16)=log(8) | | -12(-9x+23)=480 | | v=34000-0.2m | | 0=x-7x^(1/7) | | 0=1-x^(-6/7) | | 5x-10=2(8x+6) | | 882=9(-9x-10) | | 0.60x+0.15(80)=0.50(x+80) | | 4a+20=5b+7 | | 12(4-5x)=44 | | -0.1x+0.3y=-2 | | b^2-4b-14=-1 | | 4a-5b=-13 | | 12x-236=76+18x | | 3.4=400a+20b | | 2/5h-16=3/5h-14 | | t=7-10(39-1) | | -6x+7(-3x-34)=32 | | t=-6+4(15-1) | | 4x^2+x=-4 | | t=19+6(52-1) | | 0=8x^2+8x+1 | | 115-1/6 | | 251-17x=-9x-285 | | t=-38-7(52-1) | | -25.5=9(8.5x-6) | | 425=(2h-10)+h | | 4n^2+7n-9=0 |

Equations solver categories